n the webs of credit: wealth, power and prestige among businessmen in the nineteenth century Estancia/Sergipe (1820-1888) / Nas teias do crédito: riqueza, poder e prestígio entre os homens de negócio na Estancia/Sergipe oitocentista (1820-1888) - Sheyla Farias Silva (Universidade Estadual de Alagoas, 2019)
In studying the material life of the merchants established in Estância / Sergipe in the period of 1820- 1888, through the analysis of 75 postmortem inventories, we perceived the mercantile and dynamic character of this city, evidenced by the composition of the fortunes, in a larger portion formed by active debts, incurred through commercial exchange, supply, loans, and commercial transactions with merchants from other Sergipe communities, as well as other Provinces, like Bahia. Also according to the possession of goods, we find that some dealers had an extensive credit network, originated by the purchases made in the term in their stores or by loans granted. Considering the act of lending, even small amounts, an opportunity to expand its influence, inasmuch as for this society the usurious capital promoted prestige and power. We also found that a small group that controlled some key sectors of the local economy, such as credit and supply.